X = 3 and Y = 2. Here is how we find this.

What we have to do is use the first equation to get a value for y. This is quite easy because all we must do is say

x + y = 5 so y = 5 -x

Now we plug that value into the second equation.

2x - (5-x) = 4

This becomes

2x - 5 + x = 4 (because you are subtracting negative x, you are in effect adding x)

3x - 5 = 4

3x = 9

x = 3

If x = 3, then 3 + y = 5 and y = 2

Posted on

x+y = 5 ........(1)

2x-y = 4 .........(2)

Using the emimination method, let us add (1) and (2):

==> 3x = 9

==> x= 9/3 = 3

Now using the substituting method substotite in (1):

x+ y = 5

==> 3 + y = 5

==> y= 5-3 = 2

==> y= 2

Posted on

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now